Ethanol extract of Portulaca oleracea L. mitigates atherosclerosis through modulation of cholesterol efflux and uptake pathways - Chen, Bin; Sun, Shanshan; Fu, Jialei; Ge, Ling; Nie, Wei; Zhou, Peina; Cao, Peng; Zhou, Qian (Frontiers in Pharmacology, 2025)
BackgroundPurslane (Portulaca oleracea) is a medicinal and edible plant. Purslane extract (POEE) exhibits lipid-lowering, anti-inflammatory, and antioxidant properties. Traditionally, this extract has been used to treat various inflammatory conditions, including skin inflammation, enteritis, and dysentery. However, its therapeutic potential and molecular mechanisms in atherosclerosis (AS) remain unclear.MethodsUltra-performance liquid chromatography-quadrupole/time-of-flight mass spectrometry (UPLC-Q/TOF-MS) and the Traditional Chinese Medicine Systems Pharmacology Database were employed to identify the active components of POEE. Network pharmacology was used to predict POEE’s mechanisms for alleviating AS. An in vitro foam cell model was established by treating RAW264.7 macrophages with oxidized low-density lipoprotein (ox-LDL), and the protective effects of POEE were assessed via the 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide (MTT) assay, while intracellular lipid accumulation was identified using Oil Red O staining. Protein expression related to cholesterol metabolism was analyzed by Western blot (WB). For in vivo validation, AS was induced in rats through a high-fat diet and carotid artery injury. After 4 weeks of daily POEE administration, the therapeutic efficacy was tested by measuring serum lipid levels, cardiac function, histopathological changes, and the cholesterol transport-related protein expression.ResultsThe bioactive compounds identified in POEE were categorized into 10 groups, including flavonoids (24), terpenoids (16), phenols (6), and alkaloids (4), and others. Network pharmacology predictions implicated POEE in modulating the “Lipid and Atherosclerosis” pathway. POEE significantly reduced total cholesterol (TC) and free cholesterol (FC) levels in ox-LDL-stimulated macrophages, attenuating foam cell formation. Furthermore, POEE enhanced reverse cholesterol transport (RCT) by upregulating the expressions of ATP-binding cassette transporters ABCA1 and ABCG1 to promote cholesterol efflux, while suppressing CD36 and MSR1 expressions to inhibit cholesterol uptake. In vivo, POEE administration lowered serum triglycerides (TG), TC, FC, and LDL-C levels; elevated HDL-C; and ameliorated carotid artery lesions in AS rats. Concordantly, ABCA1 expression was upregulated and that of MSR1 was downregulated in POEE-treated carotid tissues.ConclusionPOEE alleviates atherosclerosis by enhancing RCT through regulation of cholesterol efflux and uptake pathways. POEE may be a promising therapeutic candidate for AS.